Intergenerational Transmission of Violence, Threatened Egoism, and Reciprocity: A Test of Multiple Psychosocial Factors Affecting Intimate Partner Violence - Holt, Jessica L. (American journal of criminal justice, 2008)
A myriad of factors have been advanced to explain intimate violence. This study was undertaken to investigate the effects on intimate violence of three specific concepts: threatened egoism, violence in the family of origin, and reciprocity. Self-report questionnaires were administered to a randomly selected cluster sample of 423 participants, 147 males and 276 females. While no support was found for threatened egoism, both violence witnessed in the family of origin and reciprocity were found to significantly influence intimate violence. Analyses conducted separately for males and females indicated that these factors operate differently based on gender.